1989
DOI: 10.2224/sbp.1989.17.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Attributions of Causality, Moral Responsibility, and Blame: Perceivers' Evaluations of the Attributions

Abstract: Perceivers' evaluations of attributions of causality, moral responsibility, and blame were investigated in this study. Participants read 2 scenarios with either mild or severe consequences, and then rated the perpetrators on either causality, moral responsibility, or blame. Participants subsequently rated the attributions on several evaluative dimensions. Attributions of moral responsibility were generally judged by perceivers to be more complex than attributions of causality and blame, suggesting that the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Women might have attempted to judge their husbands as being responsible before blaming them, but at the same time they might also have blamed their husbands directly without taking into account various criteria of responsibility. In a different experimental context (which consisted of two brief scenarios involving negligent acts), Bell (1989) concluded that attribution of blame toward perpetrators may not involve the subprocess of evaluating moral responsibility. In the context of close relationships, women have often been considered to be the barometer of the relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women might have attempted to judge their husbands as being responsible before blaming them, but at the same time they might also have blamed their husbands directly without taking into account various criteria of responsibility. In a different experimental context (which consisted of two brief scenarios involving negligent acts), Bell (1989) concluded that attribution of blame toward perpetrators may not involve the subprocess of evaluating moral responsibility. In the context of close relationships, women have often been considered to be the barometer of the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…There will be no significant path from causality and responsibility to marital adjustment. The justification of this second hypothesis was based mainly on the results of several studies in which the entailment model was applied to negligent acts and moral behaviors; these studies demonstrated that external outcomes are predicted by blame attributions and that the effects of causal and responsibility attributions on these outcomes are mediated by blame attributions (Bell, 1989; Shultz et al, 1986).…”
mentioning
confidence: 99%
“…Although these models hold that there is a clear relation between moral responsibility and blame, there is a dissenting perspective that indicates that responsibility and blame are more distinct (Bell, 1989;Brems & Wagner, 1994). Specifically, based on empirical findings of perceiver ratings of negligent actions, the authors concluded that moral responsibility is likely not evaluated in the process of assigning blame and that responsibility is in fact a more complex process.…”
Section: Attribution Theory: Definition Types and Construct Relationsmentioning
confidence: 99%
“…II apparaît plausible d’émettre l’hypothése qu’à la fois les variables d’attribution et les indices de détresse psychologique seront associés de facon significative aux cotes d’ajustement dyadique. De plus, en se basant sur plusieurs recherches qui ont appliqué le modéle emboîté des attributions à l’étude de divers comportements de négligence, de préjudice et de colére (Bell, 1989; Fincham & Bradbury, 1992; Shultz, Wright, & Scheilfer, 1986), il y a tout lieu de croire que le blâme sera la variable d’attribution la plus étroitement reliée à l’ajustement conjugal, comparativement à la causalité et à la responsabilité. Également, selon le modéle multidimensionnel de la détresse psychologique, nous croyons que des indices de santé mentale autres que la dépression (par ex., agressivité, anxiété et problémes cognitifs) viendront expliquer une portion significative de la variance associée à l’ajustement conjugal.…”
unclassified